2021
DOI: 10.3390/ijerph18147655
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter and Premature Mortality: A Bayesian Meta-Analysis

Abstract: Background: We present a systematic review of studies assessing the association between ambient particulate matter (PM) and premature mortality and the results of a Bayesian hierarchical meta-analysis while accounting for population differences of the included studies. Methods: The review protocol was registered in the PROSPERO systematic review registry. Medline, CINAHL and Global Health databases were systematically searched. Bayesian hierarchical meta-analysis was conducted using a non-informative prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Particulate matter smaller than or equal to 2.5 microns in diameter (PM 2.5 ) causes cardiovascular and respiratory diseases and is responsible for over 4 million premature deaths per year globally. In urban environments, sulfate is a major contributor to particulate mass, accounting for 20% of PM 2.5 on average. , Air quality models often underestimate sulfate concentrations in polluted regions on the order of 2–6× lower than the observed ambient concentrations, suggesting unaccounted for primary sulfate emissions or secondary sulfate formation mechanisms in these environments. …”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter smaller than or equal to 2.5 microns in diameter (PM 2.5 ) causes cardiovascular and respiratory diseases and is responsible for over 4 million premature deaths per year globally. In urban environments, sulfate is a major contributor to particulate mass, accounting for 20% of PM 2.5 on average. , Air quality models often underestimate sulfate concentrations in polluted regions on the order of 2–6× lower than the observed ambient concentrations, suggesting unaccounted for primary sulfate emissions or secondary sulfate formation mechanisms in these environments. …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PM 2.5 affects the respiratory and cardiovascular systems, causes a range of other detrimental health effects and is responsible for several million global deaths every year. 1,2 Despite greater knowledge about the impacts of air pollution on morbidity and mortality, the number of global deaths attributable to ambient PM 2.5 has risen by 102% from 1990 to 2019. 3 In 2020, the Health Effects Institute estimated that air pollution was the 4th leading risk factor for all deaths across the globe, making air pollution the leading environmental risk factor for premature death.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated cardiovascular diseases associated with air pollution exposure, which is reported in the recent times, is linked to the toxicity induced by particulate matter (PM) present in the pollutant [ 1 ]. Recent publications have reported that PM 2.5 (PM < 2.5 μm in size) accounted for nearly 200,000 premature deaths annually [ 2 ]. Inhaled PM contains a fraction of inorganic/metals and organic/polycyclic aromatic hydrocarbons that are associated with oxidative stress and inflammation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%